Clinical manifestations of allergic rhinitis in children at Denpasar Hospital - Gary Adhianto; Hendra S (Indonesian Pediatric Society, 2001)
This is a retrospective study by collecting data from the medical record of children diagnosed as allergic rhinitis at the Pediatric Allergy & Immunology out patient clinic at Denpasar Hospital between January 1996 and December 2000. Reported data including identifying patient, signs and symptoms, atopic history of the family, skin prick test (SPT) result and the environmental factors. Fifty-five from 297 children (18.5%) attending the Pediatric Allergy & Immunology out patient clinic were diagnosed as allergic rhinitis. Thirty nine were male and 16 female. The age ranged from 6 months to 15 years old. The majority of signs and symptom were sneezing and rhinorrhea (26%), itchy nose (23%), blocked nose (14%) and itchy eyes(12%).. Four children had history of atopic dermatitis, 1 food allergy, 10 asthma, 3 urticaria, 2 drug allaaaergy, 4 h-ad history of both atopic dermatitis and urticaria, 13 both asthma and urticaria, 2 both asthma and drug allergy and 6 children had no history of allergic diseases. Thirty three (60%) one of the parents and 12 (21.8%) both parents ever had allergic diseases. According to SPT, 27 (55.1%) of this children had positive reaction to inhalant allergen, 13 (26.5%) to food allergen and 13 (26.5%) had negative reaction.